Structural-semantic peculiarities of causative adverbs in Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article analyzes structural-semantic peculiarities of causative adverbs which are singled out of adverbial modifiers. The research defines quantitative composition of causative adverbs. The adverbs with causative semantics are grouped according to causal shades of meaning.
Keywords: causativity; causality; cause; causative construction; adverb